Informasi Anatomi MSCT Sinus Paranasal pada Suspek Sinusitis dengan Variasi Rekonstruksi Algorithma - Sri Mulyati; Gatot Murti Wibowo; Jeffri Ardiyanto; Sylvia Ishlahul Ummah (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: The standard operating procedure with the bone window technique and bone reconstruction algorithm is referred to the MSCT protocol for paranasal sinuses in Hospital. However, the majority of radiologists select a protocol that implements the algorithm reconstruction, which is still trial and error without an organized protocol development study. There is a chance that the accuracy of the MSCT SPN and the quality of the picture data may become crucial problems. This study set out to assess and examine the algorithmic reconstruction method that can yield more accurate SPN anatomical data in sinusitis suspects.Methods: A quasi-experimental technique was taken in conducting the research. Three filters (bone, boneplus, and edge) of the reconstruction method were used to get thirty SPN images from ten patients. The images were  assessed by the two expert radiologist.Results: The results of non-parametric was obtained based on statistical tests using the  Friedman test ρ-value  of anatomy, namely 0.00 less than 0.05. These results indicate that H0 is rejected and Ha is accepted,  meaning that there are differences in anatomical information between variations of bone, boneplus, and  edge reconstruction algorithms on the MSCT scan examination of the paranasal sinuses with sinusitis suspect. The Friedman test results using the mean rank values of each anatomy show that Boneplus is  superior in terms of visualizing anatomy. The Friedman test's mean rank value of the entire anatomy  yielded the result that the boneplus reconstruction algorithm is superior to the bone and edge reconstruction algorithm in displaying anatomical information on the MSCT scan of the paranasal  sinuses with sinusitis suspect.Conclusions: Based on value mean rank For each Friedman test anatomy and the results of the frequency distribution, variations of the bone plus reconstruction algorithm are more optimal in displaying anatomical information on the MSCT Scan of the paranasal sinuses compared with the edge and bone reconstruction algorithms.